Building A Mean-state Of Oceanographic Properties (Temperature And Salinity) For The Kwazulu-natal Bight Using The Roms Model: A Contribution Towards Marine Protected Areas Analysis - Malange, Mathabo Noxolo (Department of Oceanography, 2020)
The KwaZulu-Natal Bight, located along the east coast of South Africa, is an important recruitment and nursery area for various marine species. In an effort to conserve a number of threatened species, two Marine Protected Areas (MPA) have been established in the Bight. The African Coelacanth Ecosystem Programme is conducting MPA analyses along the Bight through a series of biological and oceanographic studies and this study forms part of the oceanographic research component that will assist in the decision-making process of MPAs in the region. This study uses a 30-year, high-resolution, regional ROMS simulation to build a climatology representative of the mean-state of the Bight. The model is also used to investigate the seasonal and annual variability as well as the influence of the Agulhas Current on the shelf. The Bight was cooler and less saline than the surrounding waters and seasonal variation was limited to the upper 50 m of the water column. The depth of the Bight ranges from 50 m in the inner shelf to 100 m at the shelf edge in the central region of the Bight. In the northern and southern region of the Bight, the depth of the water column extends down to about 150 m at the shelf edge. In summer, surface temperatures were on average 4.8°C and 4.3°C warmer than in winter over the uThukela Banks and Aliwal Shoal respectively. Bottom temperatures at both MPAs had a mean seasonal variation of about 3°C. Salinity, a more conservative variable, showed little variability over the year throughout the water column except for at 50 m where lower salinities were observed in the winter months. Wavelet analysis showed that a strong annual (12 month) signal was dominant at the surface (10 m). Bottom temperatures displayed a weaker annual signal than the surface in addition to a slight semi-annual cycle. Further investigations indicated that the Agulhas Current influenced the Aliwal Shoal MPA more than the uThukela Banks MPA as they shared similar temperature values (at the surface and bottom) throughout the 30-year period. In contrast, the uThukela was cooler than the Agulhas Current by 0.5 to 1.5°C at the surface and 1 to 2.5°C at the bottom. These time series also enabled us to identify anomalous features such as the Natal Pulse that could have important implications for temperature-sensitive species in the area.